CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF THE ORGANS OF THE DENTITION IN CHILDREN WITH DISORDERS OF THE UPPER RESPIRATORY SYSTEM - Gafforov Sunnatullo Amrulloevich, Durdiev Jonibek Ismatovich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The maxillofacial system (MLS) is a part of the body that dynamically changes during development and growth [3], where there is an interaction between genes, hormones, epigenetic factors and these factors determine the formation of the bone morphology of the craniofacial region, the violation of which may entail irreversible changes in this area [7, 8, 6,11, 22, 26, 35].